CARACTÉRISATION D’UN BASSIN SÉDIMENTAIRE À L’AIDE D’UNE ANALYSE STRUCTURALE : CAS DU BASSIN GRÉSEUX DE L’INKISI AFFLEURANT À KINSHASA (RDC) - Bamulezi, Gloire Ganza; Bibentyo, Toussaint Mugaruka; Birhenjira, Espoir Mugisho (European Scientific Journal, ESJ, 2014)
Structural analysis of data on the bedding planes orientation and oblique litages observed in the Inkisi sedimentary Basin flush in Kinshasa and its immediate surroundings has allowed to make the characterization of the basin. The paleocurrent orientation in origin of the setting up of sediments shows that the source of sediments (Chaillu Massif in Gabon) is located in the north of the basin, and the palaeoslope of the basin (10 ° -20 °) is not very hilly. These structural parameters obtained using the Win-tensor software (version 5 .0.2 ) have strengthened the hypothesis on the fluviodeltaic nature of the basin which had been issued by Alvarez and his companions in 1995.